2011
DOI: 10.1002/eqe.1174
|View full text |Cite
|
Sign up to set email alerts
|

Shake‐table tests of a three‐story reinforced concrete frame with masonry infill walls

Abstract: SUMMARY This paper presents the shake‐table tests of a 2/3‐scale, three‐story, two‐bay, reinforced concrete frame infilled with unreinforced masonry walls. The specimen is representative of the construction practice in California in the 1920s. The reinforced concrete frame had nonductile reinforcement details and it was infilled with solid masonry walls in one bay and infill walls with window openings in the other bay. The structure was subjected to a sequence of dynamic tests including white‐noise base excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(71 citation statements)
references
References 14 publications
1
67
0
2
Order By: Relevance
“…At the local level, infill causes asymmetry and concentration of the frame deformation. Stavridis et al [14] conducted shaking table test of a three-story RC frame infilled with solid masonry walls in one bay and infill walls with window openings in the other bay and found that infill walls with openings are much more vulnerable to collapse than solid walls.…”
Section: Introductionmentioning
confidence: 98%
“…At the local level, infill causes asymmetry and concentration of the frame deformation. Stavridis et al [14] conducted shaking table test of a three-story RC frame infilled with solid masonry walls in one bay and infill walls with window openings in the other bay and found that infill walls with openings are much more vulnerable to collapse than solid walls.…”
Section: Introductionmentioning
confidence: 98%
“…4 [12]. The paper by Stavridis is sufficiently detailed by providing the necessary geometric and material properties as well as test results to develop a FE model.…”
Section: A Experimental Test Structurementioning
confidence: 99%
“…These towers did not interact with the structure during the tests as they were placed with a 2-cm gap from the specimen. Further details on the design and configuration of the specimen and the shake table tests can be found in Stavridis (2009) and Stavridis et al (2012).…”
Section: -Story Infilled Rc Framementioning
confidence: 99%